Perancangan Strategi Pemasaran Merek Kosmetik Emina dengan Pendekatan Design Thinking - Melati Sasabila; Sani Ega Priani (UNISBA Press, 2022)
Abstract. Emina Cosmetics is one of the cosmetic brands from the company PT Paragon Technology and Innovation. With the increasingly fierce competition in the cosmetics industry, a marketing strategy is needed to attract consumers to use Emina Cosmetics products. This study aimed to determine the user persona, empathy board, marketing strategy, and their success through the design thinking method. Based on the research that has been done, it is found that the user persona of the cosmetic brand Emina is a female teenager aged 13-18 years with a middle-class socioeconomic and living in an urban area in Indonesia. The empathy map results show that consumers want skincare products at affordable prices and formulas suitable for their skin. The most appropriate and relevant marketing strategy design for the cosmetic brand Emina with a design thinking approach is to design a marketing campaign with the main message #BestBuddies, which is divided into three stages, namely the trigger stage, the experience stage, and the amplify stage. The design of this marketing strategy shows good results referring to the results of the interviews Abstrak. Emina Cosmetics merupakan salah satu merek kosmetik dari perusahaan PT Paragon Technology and Innovation. Dengan persaingan industri kosmetik yang semakin ketat, diperlukan strategi pemasaran yang mampu menarik konsumen untuk menggunakan produk Emina Cosmetics. Tujuan dari penelitian ini adalah mengetahui user persona, empathy board, strategi pemasaran, dan keberhasilannya melalui metode design thinking. Berdasarkan penelitian yang telah dilakukan, didapatkan user persona merek kosmetik Emina adalah remaja wanita berusia 13-18 tahun dengan sosioekonomi kelas menengah dan tinggal di daerah urban di Indonesia. Hasil dari empathy map adalah konsumen menginginkan produk perawatan kulit dengan harga terjangkau dan mempunyai formula yang cocok di kulit mereka. Adapun rancangan strategi pemasaran yang paling tepat dan relevan untuk merek kosmetik Emina dengan pendekatan design thinking adalah merancang marketing campaign dengan pesan utama #BestBuddies yang dibagi menjadi tiga tahap, yaitu tahap triggers, tahap experience, dan tahap amplify. Perancangan strategi pemasaran ini menunjukkan hasil yang baik merujuk pada hasil wawancara.